2015
DOI: 10.1038/nature14093
|View full text |Cite|
|
Sign up to set email alerts
|

Probabilistic reanalysis of twentieth-century sea-level rise

Abstract: Estimating and accounting for twentieth-century global mean sea level (GMSL) rise is critical to characterizing current and future human-induced sea-level change. Several previous analyses of tide gauge records--employing different methods to accommodate the spatial sparsity and temporal incompleteness of the data and to constrain the geometry of long-term sea-level change--have concluded that GMSL rose over the twentieth century at a mean rate of 1.6 to 1.9 millimetres per year. Efforts to account for this ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
465
1
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 530 publications
(499 citation statements)
references
References 37 publications
32
465
1
1
Order By: Relevance
“…There have not yet been any new comprehensive attempts to close the budget since 1993 with the revised satellite altimeter data, nor have there been any new assessments of the budget of GMSL rise before the satellite altimeter period. Hay et al [17] suggested that their lower rate of twentieth century GMSL rise is more consistent than earlier reconstructions with the sum of contributions. We note that there are several possible combinations of the contributions presented by Gregory et al [83] that could match the reconstruction of Hay et al Moreover, their estimated rate of sea level rise prior to 1950 is slightly larger than that of Church and White [18].…”
Section: The Sea Level Budgetmentioning
confidence: 65%
See 3 more Smart Citations
“…There have not yet been any new comprehensive attempts to close the budget since 1993 with the revised satellite altimeter data, nor have there been any new assessments of the budget of GMSL rise before the satellite altimeter period. Hay et al [17] suggested that their lower rate of twentieth century GMSL rise is more consistent than earlier reconstructions with the sum of contributions. We note that there are several possible combinations of the contributions presented by Gregory et al [83] that could match the reconstruction of Hay et al Moreover, their estimated rate of sea level rise prior to 1950 is slightly larger than that of Church and White [18].…”
Section: The Sea Level Budgetmentioning
confidence: 65%
“…There are now more estimates of acceleration of GMSL over the nineteenth to twentieth century and these are generally larger than those available at the time of the AR5, ranging from 0.0042±0.0092 [15] to 0.02±0.01 mm year −2 [16] (see Cahill et al [29]; Hay et al [17]; Hogarth [30]; Olivieri and Spada [31]; Spada et al [32] for intermediate estimates). Jorda [33] estimated that at least 2.2 mm year −1 of the recent sea level trend estimated from altimetry cannot be attributed to unforced multidecadal variability, implying that the change in trend between 1900 and 1990 and the altimeter period is at least partly forced.…”
Section: Historical Sea Levelmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the vertical stability of the Australian continent and its suitability as a datum for MSL observations has been debated for decades [e.g., Emery, 1986, 1988;Bryant et al, 1988;Amin, 1993;Belperio, 1993;Feng et al, 2004;Sandiford, 2007;Moucha et al, 2008;Watson, 2011;Lewis et al, 2012]. Hay et al [2015], Haigh et al [2014], Hogarth [2014], Holgate and Woodworth [2004], Jevrejeva et al [2014], Jorda [2014], Merrifield et al [2009], Olivieri and Spada [2013], Watson et al [2015], and Woodworth et al [2009Woodworth et al [ , 2011; those that claim deceleration include Boretti [2012], Boretti and Watson [2012], Parker et al [2013], and Watson [2011]; those that claim neither include Schr€ oter [2010, 2014].…”
Section: Introductionmentioning
confidence: 99%